MODEL PENDIDIKAN PESANTREN TERPADU DALAM MEMBINA KARAKTER DI ERA GLOBALISASI (Pascasarjana IAIN Kudus, 2019)
Growing character is one of the most important goals that must be achieved in all educational processes. Therefore all educational institutions must have the best model in the character internalization process for each student. The purpose of this study was to describe a model of character-based education. This research is a qualitative research with a qualitative descriptive approach. The object of research that is the focus of analysis is Islamic Boarding Schools. Rahmaniyah Al-Islamy, Bogor, West Java. The method used is natural objects and natural data collection by participant observation. The results of the data if the research shows that the Rahmaniyah Al Islami Islamic Boarding School implements an integral character-based education model that includes aspects of aqeedah, spiritual, physical and intellect. The process of character internalization through a comprehensive approach, habituation, exemplary, discipline and civilization.